2021
DOI: 10.25259/sni_19_2021
|View full text |Cite
|
Sign up to set email alerts
|

Tranexamic acid to reduce operative blood loss in brain tumor surgery: A meta-analysis

Abstract: Background: Major blood loss during neurosurgery may result in a variety of complications, such as potentially fatal hemodynamic instability. Brain tumor and skull base surgery is among the high bleeding risk procedures. Tranexamic acid (TXA) has been found to reduce bleeding events in various fields of medicine. Methods: We searched for all randomized controlled trials published in English or Bahasa which compared the use of TXA with placebo in brain tumor surgery. The studies should include adult patient… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 40 publications
0
2
1
Order By: Relevance
“…Another recent meta-analysis including three studies and 200 patients showed a reduction of peri-operative blood loss when TXA was used (mean difference of −292.8 ml; 95% CI −431 to −153 ml; P < 0.05). However, the use of blood transfusion was not significantly changed in the TXA cohort 957 . This is in contrast to a recent RCT in which 30 patients underwent meningioma resection with and without TXA treatment.…”
Section: Discussioncontrasting
confidence: 85%
See 1 more Smart Citation
“…Another recent meta-analysis including three studies and 200 patients showed a reduction of peri-operative blood loss when TXA was used (mean difference of −292.8 ml; 95% CI −431 to −153 ml; P < 0.05). However, the use of blood transfusion was not significantly changed in the TXA cohort 957 . This is in contrast to a recent RCT in which 30 patients underwent meningioma resection with and without TXA treatment.…”
Section: Discussioncontrasting
confidence: 85%
“…However, the use of blood transfusion was not significantly changed in the TXA cohort. 957 This is in contrast to a recent RCT in which 30 patients underwent meningioma resection with and without TXA treatment. In this study, a clear benefit of TXA was shown in terms of less blood loss (616 AE 393 versus 1150 AE 416 ml).…”
Section: Intracranial Surgerymentioning
confidence: 76%
“…Tranexamic acid (TXA) is a commonly used antifibrinolytic drug, which can inhibit the conversion of single‐chain tissue plasminogen activator (set‐PA) to its double‐chain form (tct‐PA) by plasmin, 1 thereby inhibiting fibrinolysis and reducing bleeding. At present, TXA has been widely used in orthopedics surgeries, 2 , 3 brain surgeries, 4 gynecological surgeries, 5 and so on. Among orthopedic surgeries, TXA was used in joint replacement, 6 , 7 fracture surgery, 8 spinal surgery 9 and osteotomy 10 , 11 to reduce perioperative blood loss and transfusion requirements.…”
Section: Introductionmentioning
confidence: 99%